Mills’ syndrome: a case report - Fábio Henrique de Gobbi Porto; Marco Orsini; Marco Antônio Araújo Leite; José Moreira dos Santos; Soraia Pulier; Mariana Mello; Osvaldo J.M. Nascimento (Neurology International, 2009)
The syndrome of progressive, ascending or descending hemiplegia, with no significant sensory impairment was first describes by Mills in 1900, which several cases were reported later. However after diagnostic tests and image improvements, the number of reports has shortened. A possible explanation for this shortage is the identification of other diseases that could mimic the clinical picture. Currently, the syndrome has an uncertain nosological status, since it was described based on clinical examination only. We can find this clinical presentation (Mills syndrome) in cases of amyotrophic lateral sclerosis (ALS), predominant upper motor neuron amyotrophic lateral sclerosis (UMN-ALS) and primary lateral sclerosis (PLS), besides its symptomatic (secondary) forms. We describe a case (initial presentation and one year follow-up) of progressive ascending hemiplegia with clinical isolated upper neuron signs and normal sensory examination, discussing its nosological status, electromyographic findings, differential diagnosis and prognosis.